Effects of prenatal alcohol exposure on language, speech and communication outcomes: a review longitudinal studies. Issue 2 (19th November 2018) - Hendricks, Gaironeesa; Malcolm-Smith, Susan; Adnams, Colleen; Stein, Dan Joseph; Donald, Kirsten Ann Mary
Abstract: Objective: The aim of this paper was to provide a systematic review and update on the available longitudinal studies on the impact of prenatal alcohol exposure (PAE) on language, speech and communication development, as well as associated potential environmental confounders during the preschool period. Methods: A literature search was restricted to English, full‐text, peer‐reviewed, longitudinal studies in from 1970 until present: PUBMed, Scopus, Web of Science {C-e Collection, Biological Abstracts, KCI-Kean Journal Database, Russian Science Citation Index, SciELO Citation Index, Zoological Rec-d}, Academic Search Premier (Africa-Wide Information, CINAHL, MEDLINE, PsycINFO. Keywords included: prenatal alcohol exposure (PAE); speech or language or communication outcomes; neurocognitive or neurodevelopment or neurobehavioral or neurobehavioural; infant or baby or toddler or preschooler; longitudinal or follow-up. The inclusion criteria included (i) longitudinal cohorts with at least 2 time-points; (ii) association of light, moderate or heavy PAE on language, speech or communication delay, development or disorder; (iii) environmental confounders; (iv) infants up to preschool age. Results: Six studies satisfied the threshold for inclusion. Three studies reported that PAE was significantly associated with receptive or expressive delay. These studies demonstrated lower scores on either receptive or expressive communication in the alcohol group in comparison to the non-alcohol group, even after controlling for environmental factors up to 36 months. Conclusion: Evidence from the longitudinal studies reviewed suggest that PAE influenced delays in receptive and expressive communication up to 36 months. Contextual risk factors played a significant role in language development over time and especially as children approached school age.